Employee Self-Efficacy and Productivity in Selected Trading Companies: Basis for Action Plan - Espelita, Cherry Ann Marie H. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the relationship between self-efficacy and employee productivity in selected trading companies in Laguna, Philippines. It utilized a quantitative, descriptive-correlational design with 187 purposively sampled full-time employees. Five dimensions of self-efficacy (general, occupational, task-specific, entrepreneurial, and work environment support) were analyzed against five productivity indicators (task completion, quality of work, problem-solving, collaboration, and initiative). Validated survey instruments yielded high internal consistency (Cronbach’s alpha > 0.86). Results showed moderate levels of self-efficacy and productivity. Significant positive correlations existed between all dimensions, with Work Environment and Support emerging as the strongest predictor of productivity (β = 0.395, p < 0.001). Regression analysis explained 73.8% of productivity variance (R² = 0.738). The findings underscore the importance of fostering a supportive work environment and tailored interventions to enhance productivity in the trading sector.